Microleakage, adaptation ability and clinical efficacy of two fluoride releasing fissure sealants - Marković Dejan; Petrović Bojan; Perić Tamara; Blagojević Duška (Vojnosanitetski Pregled, 2012)
Background/Aim. Retention of fissure sealants and good adaptation to enamel are essential for their success. Fluoride releasing resin-based materials are widely accepted for pit and fissure sealing, but newly designed glass ionomers can serve as a good alternative. The aim of this study was to evaluate microleakage and sealing ability in vitro, and to clinically assess two fluoride releasing fissure sealants. Methods. The sample for experimental study consisted of 20 freshly extracted intact human third molars, divided in two experimental groups according to the sealing material: fluoride releasing resin-based (Heliosel F) and glass ionomer (Fuji Triage) material. Digital images and scanning electron microscope were used to assess microleakage and adaptation ability. Sample for clinical study consisted of 60 children, aged 6-8 years, with high caries risk, divided in two groups according to the sealant material. Fissure sealant was applied to all erupted, caries-free first permanent molars. Sealants were evaluated after 3, 6 and 12 months using modified Ryge criteria for retention, marginal adaptation, colour match, surface smoothness and caries. Results. Microleakage was detected in more than half of the specimen, without significant differences between the two groups (p > 0.05). Both materials exhibited acceptable sealing ability. Complete retention at the end of the observation period was 81.8% for resin-based, and 21.1% for glass-ionomer fissure sealant (p < 0.001). The presence of caries in sealed molars has been detected in one patient in both groups. During the 12-month observation period, Helioseal F demonstrated better retention, marginal adaptation and surface smoothness (p < 0.001). There were no differences between the two materials regarding caries and color match (p > 0.05). Conclusion. Both tested materials demonstrate satisfactory clinical and caries prophylactic characteristics that justify their use in contemporary preventive dentistry.